(untitled) (Olhar de Professor, 2022)
This article presents the results of the Internal Knowledge Leveling Olympiad (OINC) developed in the Escola Cidadã Integral Senador Rui Carneiro, due to the concern of the school staff about the students’ demotivation, besides the teachers’ own insecurities in the pandemic period of remote classes. The educational and theoretical-methodological options are linked to the method of Integral Citizen Schools (ECIs) and the active teaching-learning methodologies. The research was qualitative. The OINC was applied in three phases with all students in the school who had access to the internet. The negative points observed were the lack of internet access and the feeling of exclusion of students who could not participate. The positive points were the increase in student motivation and the rescue of idle and absent students. It is concluded that the experience enabled the reintegration of students and increased the hope of the school staff in times of crisis and uncertainty.